2009
DOI: 10.1164/rccm.200807-1064oc
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lung Injury Is Reduced in fat-1 Mice Endogenously Synthesizing n-3 Fatty Acids

Abstract: fat-1 Mice exhibited reduced features of ALI and sickness behavior. Increasing the availability of n-3 FA may thus be beneficial in critically ill patients with ALI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 63 publications
3
42
0
Order By: Relevance
“…The fat-1 mouse model has been used extensively as an approach to increase tissue n-3 PUFA levels [30,31,[46][47][48][49][50][51][52][53]. In regards to the brain, expression of 4.2% of 25,000 measured genes are altered in the fat-1 mouse [54]; fat-1 mice have increased hippocampal neurogenesis and spatial learning performance [31], and they are protected in the pentylenetetrazol seizure model [30].…”
Section: Discussionmentioning
confidence: 99%
“…The fat-1 mouse model has been used extensively as an approach to increase tissue n-3 PUFA levels [30,31,[46][47][48][49][50][51][52][53]. In regards to the brain, expression of 4.2% of 25,000 measured genes are altered in the fat-1 mouse [54]; fat-1 mice have increased hippocampal neurogenesis and spatial learning performance [31], and they are protected in the pentylenetetrazol seizure model [30].…”
Section: Discussionmentioning
confidence: 99%
“…Mayer et al [7] examined the effect of n-3 versus n-6 fatty acids in a murine model of ALI comparing transgenic fat-1 to wild-type mice, avoiding possible confounding effects of enteral or parenteral nutrition (exogenous supply of lipids may modulate the inflammatory response via the neuroendocrine axis, the vagus nerve, and acetylcholine receptors on leukocytes).…”
Section: Animal Studiesmentioning
confidence: 99%
“…For example, a mouse model has been generated, which carries a transgene for the C. elegans -3 fatty acid desaturase enzyme that converts -6 PUFAs to -3 PUFAs in its tissues [65] . Thus, well-controlled experiments that avoid potentially confounding factors inherent in dietary intervention studies have been carried out with these mice to study the role of EPA/DHA in a variety of disorders, including colitis [66] , ocular neovascularization [67] , prostate cancer [68] , and acute lung injury [69] . An important study that has yet to be reported is the phenotype of these mice with respect to CVD traits, which should provide direct evidence for the effects of -3 PUFAs on atherosclerosis in an animal model.…”
Section: Conclusion and Future Implications For Nutrigenetics Of Pufmentioning
confidence: 99%